PENGELOLAAN DATA SISTEM ALIRAN DRAINASE KOTA Studi Kasus : Jakarta Selatan dan Jakarta Timur - Indriatmoko, Robertus Haryoto; Wahjono, Heru Dwi; Yudo, Satmoko (Center for Environmental Technology, 2005)
Fast growing development at big cities such as Jakarta usually cause surface hydrology problems, which is indicated by many surface detention and local floods during rainy season. These problems were raised because of the increasing of runoff coefficient of sub catchment areas and limited capacity of existing drainages. Analysis have made on drainage capacity of sub catchment areas connected to peak flow cause by rain on certain recurrence period and result in data to evaluate drainage capacity to solve these water detention and local floods problems.Ã‚Â Katakunci : Genangan, Banjir, Drainase, DAS, Database.